Developing an Interactive Multimedia of Reading for Junior High School Students Grade VII - Nini Wahyuni (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
The aim of this research is to develop an interactive learning multimedia of reading for grade VII students of SMP N 1Piyungan, Yogyakarta. This research is a research and development (R&D) study. The development of the interactive learningmultimedia of reading was carried out through several steps, namely needs analysis, course grid design, product development,product validation, product revision, try-out, and final product development. There were some respondents involved in the study, i.e.one content expert and one media expert, 75 students or needs analysis, and 48 students for try-out. The data were collected throughclassroom observation, interview, and questionnaire. The instruments of data collection were observation guides, interview guides,expert validation sheets, and questionnaires for the students. The data were analyzed descriptively. The needs analysis data show thatthe students have various needs in learning reading through the interactive learning multimedia. For the learning needs, the studentschose various reading topics, such as hobbies (73.81%), stories (54.76%), things around us (42.86%), life in school (27.38%), andteenage life (26.19%). Some of them (40.48%) preferred reading text with 100-200 words of length. Meanwhile, for the target needs,the students preferred learning reading to improve their vocabulary (71.43%), find the main idea (58.33%), find the moral (47.62%),find the general information (48.81%), and find the meaning of words in the reading text. Some of them preferred the pictured-cueditem (46.43%), the multiple-choice (44.05%), matching (40.47%), the comprehension questions (40.47%), the short-answer (40.48%),and the ordering tasks (29.76%) for the reading learning activities. Besides, the appropriate interactive learning multimedia ofreading for grade VII students in junior high schools consisted of four reading units, namely Things around Us (descriptive text),Professions (descriptive text), Foods and Drinks (procedure text), and Hobbies (procedure text). Every unit made up of the fivecomponents: Playing with Words, Let’s Read , Did You Know, Upgrade Your Reading, and Mini Dictionary. The experts’ validation datashow that the developed interactive learning multimedia of reading was "good" based on a total mean of 4.17 on a 5-1 Likert scale.The content aspect data analysis results show a mean of 4 and the media aspect shows a mean of 4.35. In addition, the results of thetry-out indicate that the content aspect is in the "good" category with the mean of 4.01, the presentation aspect is in the "good"category with the mean of 3.83, and the media aspect is in the "good" category with the mean of 4.01.